Norepinephrine release in the heart atria of diabetic rats - Kuncová, J; Slavíková, J; Svíglerová, J (General physiology and biophysics, 2003)
The content, release and uptake of norepinephrine (NE) in the sympathetic nerves of the rat heart atria were studied in the course of diabetes and in age-matched controls. Diabetes was induced by streptozotocin (STZ) and rats were subjected to further experiments 1, 4 or 7 months later (STZ1, STZ4, STZ7). Isolated atria were superfused with oxygenated Krebs-Henseleit (KH) solution. After equilibration, four 10-min fractions were collected: B1, basal release of NE; S1, potassium-evoked release (KER), where NE outflow was stimulated by depolarisation with 50 mmol/l KCl; B2, basal release of NE under the influence of the neuronal uptake blocker desipramine (DES); S2, KER under the influence of DES. The content of NE was measured by radioimmunoassay. In STZ4 and STZ7 rats, NE concentrations were significantly lower in both atria compared to controls. B1 and S1 were significantly higher in STZ4 than in control atria. DES increased KER of NE in controls only. In contrast, DES caused a significant decrease in B2 and S2 in STZ4 atria, suggesting that a substantial portion of NE release was due to a calcium-independent carrier-mediated process. In experiments with calcium-free KH solution in fractions B2 and S2, KER ill controls was nearly abolished. However, in STZ4 and STZ7 atria, S2 was still significantly higher than B2. In conclusion, the NE-releasing mechanism may be different in the chronically diabetic animals than in healthy subjects and may contribute to the decreased NE concentration in the STZ atria.
Keywords: streptozocin; Animals; experimentální diabetes mellitus; Female; Sympathetic Nervous System; hyperkalemie; Rats, Wistar; ženské pohlaví; srdeční síně; noradrenalin; fyziologická adaptace; vápník; sympatický nervový systém; progrese nemoci; Calcium; Disease Progression; Adaptation, Physiological; Heart Atria; krysa rodu Rattus; Streptozocin; zvířata; Hyperkalemia; Rats; Norepinephrine; potkani Wistar; Diabetes Mellitus, Experimental